From Querulous to Suicidal: Self-immolation in Public Places as a Symbolic Response to the Feeling of Injustice - Lévy, Benjamin T.; Prudent, Cécile; Liétard, Florian; Evrard, Renaud (Frontiers in Psychology, 2017)
Aim : This paper sheds light on the context which leads some querulous patients to self-immolate in front of, or into, public buildings (e.g. tribunals, city halls, employment agencies). Method : The author defines paranoid querulousness. A psychoanalytic perspective, but also a judicial and a psychiatric point of view over querulous claimants are presented. The links between political or social claims and self-immolation are studied. The expression of suicidal thoughts voiced by 4 querulous subjects is analyzed. 8 examples of self-immolation are presented. Results : The querulous subjects’ self-aggressive behaviors seem to be caused by a loss of hope to obtain compensation for a prejudice they allegedly suffered. Querulous individuals tend to self-immolate in front of, or into, public buildings when no answer is given to their claims. These gestures may be both a consequence of some personal distress and triggered by a difficult social or professional context. Discussion : 5 sets of assumptions derived from Freudian and Lacanian psychoanalytic theories are advanced. The status of the object over which the querulous claimants wish to assert their rights is clarified. The meaning of self-aggressive gestures is outlined by making reference to the concepts of instinct for mastery, symbolic Other, chain of signifiers, masochism, pleasure principle and reality principle. Conclusion : Prevention of self-immolation could involve that members of the legal professions, social workers, civil servants and mental health professionnals in contact with querulous subjects openly show their will to listen to these claimants' voice: self-aggressive gestures might be avoided by supporting the querulous person’s hope to obtain compensation for the prejudice allegedly suffered.